Palladium-103 (103Pd/103mRh), a promising Auger-electron emitter for targeted radionuclide therapy of disseminated tumor cells - absorbed doses in single cells and clusters, with comparison to 177Lu and 161Tb - Hindié, Elif; Larouze, Alexandre; Alcocer-Ávila, Mario; Morgat, Clément; Champion, Christophe (Theranostics, 2024)
Early use of targeted radionuclide therapy (TRT) to eradicate disseminated tumor cells (DTCs) might offer cure. Selection of appropriate radionuclides is required. This work highlights the potential of 103Pd (T1/2 = 16.991 d) which decays to 103mRh (T1/2 = 56.12 min) then to stable 103Rh with emission of Auger and conversion electrons. Methods: The Monte Carlo track structure code CELLDOSE was used to assess absorbed doses in single cells (14-μm diameter; 10-μm nucleus) and clusters of 19 cells. The radionuclide was distributed on the cell surface, within the cytoplasm, or in the nucleus. Absorbed doses from 103Pd, 177Lu and 161Tb were compared after energy normalization. The impact of non-uniform cell targeting, and the potential benefit from dual-targeting was investigated. Additional results related to 103mRh, if used directly, are provided. Results: In the single cell, and depending on radionuclide distribution, 103Pd delivered 7- to 10-fold higher nuclear absorbed dose and 9- to 25-fold higher membrane dose than 177Lu. In the 19-cell clusters, 103Pd absorbed doses also largely exceeded 177Lu. In both situations, 161Tb stood in-between 103Pd and 177Lu. Non-uniform targeting, considering four unlabeled cells within the cluster, resulted in moderate-to-severe dose heterogeneity. For example, with intranuclear 103Pd, unlabeled cells received only 14% of the expected nuclear dose. Targeting with two 103Pd-labeled radiopharmaceuticals minimized dose heterogeneity. Conclusion: 103Pd, a next-generation Auger emitter, can deliver substantially higher absorbed doses than 177Lu to single tumor cells and cell clusters. This may open new horizons for the use of TRT in adjuvant or neoadjuvant settings, or for targeting minimal residual disease.Early use of targeted radionuclide therapy (TRT) to eradicate disseminated tumor cells (DTCs) might offer cure. Selection of appropriate radionuclides is required. This work highlights the potential of 103Pd (T1/2 = 16.991 d) which decays to 103mRh (T1/2 = 56.12 min) then to stable 103Rh with emission of Auger and conversion electrons. Methods: The Monte Carlo track structure code CELLDOSE was used to assess absorbed doses in single cells (14-μm diameter; 10-μm nucleus) and clusters of 19 cells. The radionuclide was distributed on the cell surface, within the cytoplasm, or in the nucleus. Absorbed doses from 103Pd, 177Lu and 161Tb were compared after energy normalization. The impact of non-uniform cell targeting, and the potential benefit from dual-targeting was investigated. Additional results related to 103mRh, if used directly, are provided. Results: In the single cell, and depending on radionuclide distribution, 103Pd delivered 7- to 10-fold higher nuclear absorbed dose and 9- to 25-fold higher membrane dose than 177Lu. In the 19-cell clusters, 103Pd absorbed doses also largely exceeded 177Lu. In both situations, 161Tb stood in-between 103Pd and 177Lu. Non-uniform targeting, considering four unlabeled cells within the cluster, resulted in moderate-to-severe dose heterogeneity. For example, with intranuclear 103Pd, unlabeled cells received only 14% of the expected nuclear dose. Targeting with two 103Pd-labeled radiopharmaceuticals minimized dose heterogeneity. Conclusion: 103Pd, a next-generation Auger emitter, can deliver substantially higher absorbed doses than 177Lu to single tumor cells and cell clusters. This may open new horizons for the use of TRT in adjuvant or neoadjuvant settings, or for targeting minimal residual disease.